Integrated Microfluidic Card with TaqMan Probes and High-Resolution Melt Analysis To Detect Tuberculosis Drug Resistance Mutations across 10 Genes - Suporn Pholwat (American Society for Microbiology, 2015)
ABSTRACT Genotypic methods for drug susceptibility testing of Mycobacterium tuberculosis are desirable to speed the diagnosis and proper therapy of tuberculosis (TB). However, the numbers of genes and polymorphisms implicated in resistance have proliferated, challenging diagnostic design. We developed a microfluidic TaqMan array card (TAC) that utilizes both sequence-specific probes and high-resolution melt analysis (HRM), providing two layers of detection of mutations. Twenty-seven primer pairs and 40 probes were designed to interrogate 3,200 base pairs of critical regions of the inhA, katG, rpoB, embB, rpsL, rrs, eis, gyrA, gyrB, and pncA genes. The method was evaluated on 230 clinical M. tuberculosis isolates from around the world, and it yielded 96.1% accuracy (2,431/2,530) in comparison to that of Sanger sequencing and 87% accuracy in comparison to that of the slow culture-based susceptibility testing. This TAC-HRM method integrates assays for 10 genes to yield fast, comprehensive, and accurate drug susceptibility results for the 9 major antibiotics used to treat TB and could be deployed to improve treatment outcomes. IMPORTANCE Multidrug-resistant tuberculosis threatens global tuberculosis control efforts. Optimal therapy utilizes susceptibility test results to guide individualized treatment regimens; however, the susceptibility testing methods in use are technically difficult and slow. We developed an integrated TaqMan array card method with high-resolution melt analysis that interrogates 10 genes to yield a fast, comprehensive, and accurate drug susceptibility result for the 9 major antituberculosis antibiotics.